2005
DOI: 10.1152/japplphysiol.00353.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lower capillary density but no difference in VEGF expression in obese vs. lean young skeletal muscle in humans

Abstract: Obesity is associated with lower skeletal muscle capillarization and lower insulin sensitivity. Vascular endothelial growth factor (VEGF) is important for the maintenance of the skeletal muscle capillaries. To investigate whether VEGF and VEGF receptor [kinase insert domain-containing receptor (KDR) and Flt-1] expression are lower with obesity, vastus lateralis muscle biopsies were obtained from eight obese and eight lean young sedentary men before and 2 h after a 1-h submaximal aerobic exercise bout for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
93
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 37 publications
(42 reference statements)
13
93
0
2
Order By: Relevance
“…Similar findings were previously reported for Biceps muscles of Yucatan swine on a "Western"-type diet (14). These data correlate well with previous studies in humans showing that skeletal muscles from obese compared with lean individuals have greater muscle CSAs (9,24). The increased CSAs could have a negative effect on the oxygen and substrate supply to the center of the fiber, leading to the reduced muscle performance.…”
Section: E853supporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were previously reported for Biceps muscles of Yucatan swine on a "Western"-type diet (14). These data correlate well with previous studies in humans showing that skeletal muscles from obese compared with lean individuals have greater muscle CSAs (9,24). The increased CSAs could have a negative effect on the oxygen and substrate supply to the center of the fiber, leading to the reduced muscle performance.…”
Section: E853supporting
confidence: 90%
“…Increased fiber size could diminish oxygen and substrate supply for the metabolic processes in the central area of the fiber. Skeletal muscles from obese compared with lean individuals had greater muscle cross-sectional areas (CSAs) of both type 1 and 2 fibers (9,24). Weight loss resulted in a 14 -25% decrease of the fiber CSAs of both type 1 and type 2 muscle fibers (12), supporting the idea that obesity correlates with an increase in muscle fiber area.…”
mentioning
confidence: 86%
“…Capillary rarefaction was previously associated with insulin resistance both in humans and rodents (19)(20)(21). In accordance with our findings presented herein, Flisi nski et al (43) reported reduced numbers of capillaries as well as a decreased capillary-tofiber ratio in gastrocnemius and longissimus muscle in UniNx male Wistar rats.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, the number of capillaries perfusing the muscle is positively related to peripheral insulin action (14). Moreover, reduced blood flow to the muscle is correlated with insulin resistance (15)(16)(17)(18), and insulin-resistant humans and rodents exhibit capillary rarefaction (19)(20)(21). However, it still remains unclear whether the reduction in capillaries is a cause or consequence of muscle insulin resistance (22).…”
mentioning
confidence: 99%
“…Crucial features of T2D are insulin resistance and impaired glucose disposal in muscle (11). Importantly, skeletal muscle capillaries mediate the supply of oxygen, substrates, hormones, and inflammatory cells from the circulation (20). Inadequate capillarization of skeletal muscle (SkM) may lead to relative hypoxia and an inflammatory response as well as decreased metabolism.…”
mentioning
confidence: 99%